Grammar Consciousness-Raising Activities and Their Impact on Students’ Grammatical Competence - Iskandar, Joni (Universitas Islam Negeri (UIN) Syekh Wasil, Kediri, Indonesia, 2015)
This study was to investigate the implementation of grammar consciousness-raising activities for the students’ grammatical competence. The participants were 70 students of vocational high school which were divided into 35 students in experimental group and 35 students in control group. The data were gained from pre-test and post-test. The results of posttest from the experimental and control group were compared. The findings showed that the students who were taught using grammar consciousness-raising activities had significant difference on their grammatical competence. Furthermore, the students were highly motivated in learning grammar and their grammatical competences were also increasing.